Effects of polyethylene and polypropylene microplastics on the DEP degradation mechanisms initiated by •OH and SO4•- in aquatic environments - Dandan Han; Haijie Cao; Guihong Zhao; Shengxia Duan (Ecotoxicology and Environmental Safety)
Microplastics (MPs), as emerging contaminants, are widely distributed in aquatic environments and influence the transformation and ultimate outcome of organic pollutants through adsorption and interfacial effects. This study systematically explored the degradation mechanisms of diethyl phthalate (DEP) initiated by hydroxyl radicals (•OH) and sulfate radicals (SO4•⁻), with a focus on how polyethylene (PE) and polypropylene (PP) microplastics affect these processes. Density functional theory (DFT) computations were employed to identify the transformation pathways of DEP in the presence of both radicals, and transition state theory (TST) combined with diffusion-controlled rate corrections was further applied to calculate reaction rate constants. The results indicated that microplastic adsorption altered the electronic properties of DEP, affected the reaction energy barriers, and accelerated the degradation rate. To evaluate environmental and health risks, ECOSAR and TEST were utilized to assess the ecotoxicological impacts of DEP and its degradation products. Most degradation products showed lower toxic effects on aquatic organisms in comparison to DEP, but certain intermediates, such as ethyl 2-hydroxybenzoate, exhibited increased toxicity. Some degradation products also posed potential developmental toxicity and mutagenic risks. This study highlights the importance of considering both pollutant transformation processes and microplastic interactions in environmental risk assessments. This also highlights the significance of advanced water treatment technologies. By achieving complete mineralization of pollutants, they can minimize the generation of toxic intermediate products to the greatest extent, thereby protecting aquatic ecosystems.